Establishment of Legal Mechanisms in the Fight Against Corruption in Uzbekistan - Mallaev, Normamat Ramazanovich; Djalilov, Sardor Shavkatovich (European Journal of Life Safety and Stability (2660-9630), 2021)
This article analyzes the ongoing reforms in Uzbekistan in the field of anti-corruption and anti-corruption system. The article examines the norms of corruption and the fight against it, the changes in the field of corruption and the fight against corruption in our country in recent years.Information was also provided on the content of anti-corruption regulations.